2002
DOI: 10.1002/ppp.428
|View full text |Cite
|
Sign up to set email alerts
|

Observations on a blockstream in the vicinity of Sani Pass, Lesotho highlands, Southern Africa

Abstract: Coarse slope deposits, frequently grading into blockstreams, are common throughout the Lesotho highlands, southern Africa. This paper describes one such blockstream. It is interpreted as a typical lag deposit derived from valley‐wide colluvial mantles, which contains superimposed and incorporated Late‐Pleistocene blocky material. Blocks are largely derived from local scarps but may contain a component of corestones from mobilized regolith. The widespread mantle argues against landscape‐scale glaciation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…It is written that "Previous investigations have largely attributed mountain top weathering in this region to frost shattering (e.g. Boelhouwers et al, 2002;Sumner, 2004[a]; Sumner et al, 2009)" (p. 64) and their final statements specify that "to make uncritical climatic inferences based on the presence of 'frost shattered debris' on mountain summits is wholly erroneous" (Abstract, p. 61 and see also p. 68). The weathering context is clearly stated but none of the references cited in support of their contention mention 'frost shattering' in their reports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is written that "Previous investigations have largely attributed mountain top weathering in this region to frost shattering (e.g. Boelhouwers et al, 2002;Sumner, 2004[a]; Sumner et al, 2009)" (p. 64) and their final statements specify that "to make uncritical climatic inferences based on the presence of 'frost shattered debris' on mountain summits is wholly erroneous" (Abstract, p. 61 and see also p. 68). The weathering context is clearly stated but none of the references cited in support of their contention mention 'frost shattering' in their reports.…”
mentioning
confidence: 99%
“…Lightning strike sites are identified by debris, rock surfaces that are 'freshly-fractured' or 'unweathered' (p. 65) and from evidence for recent remagnetisation, although 'older' strikes are noted on page 67 to be more difficult to identify by this latter method alone. In contrast, their critique (on pages 67 and 68 in particular) is directed against studies interpreting relict valley-slope and -floor openwork block accumulations (Boelhouwers et al, 2002;Sumner, 2004a) set in the Last Glacial (maximum approximately 21-15 ka BP). Clearly this was a period of enhanced block production and slope mobility that is not comparable to today (see Sumner, 2004a p. 300), but when encompassing the areas below the summits, as Knight and Grab intrinsically do with their critique, a point that is evidently missed is the uneven geographic distribution of relict blocks in eastern Lesotho.…”
mentioning
confidence: 99%
“…However, palaeoenvironmental interpretations of associated precipitation levels during these cold periods are conflicting. 6,8,15,31 Boelhouwers and Meiklejohn 8 suggested that some periglacial features, including large patterned ground, solifluction mantles and blockstreams ( Figure 2c) were indicative of dry, cold conditions at their time of formation, whereas typically erosional features, including nivation hollows, cirques and cryoplanation terraces are likely indicative of wetter conditions during cold periods 36 . Other scholars 11,26 have argued that similar periglacial features, including large sorted patterned ground near Mafadi Summit ( Figure 2b) and at Thabana Ntlenyana, and pronival ramparts at Thabana Ntlenyana, imply relatively high moisture availability during their formation.…”
mentioning
confidence: 99%
“…This knowledge has improved the potential for palaeoenvironmental inferences to be drawn from such features. 6,12,13 Accurate inferences could be achieved through the provision of corroborating environmental evidence, and by filling in the large temporal gaps between cold periods represented by these features 6,8,18,36 .…”
mentioning
confidence: 99%
See 1 more Smart Citation